PENGARUH TERAPI MUSIK INSTRUMENTAL TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS NANGGALO PADANG TAHUN 2019 - Susilaningsih, Dewi (Ensiklopedia of Journal, 2020)
Hypertension is high blood pressure if it has systolic pressure exceeding 140 mmHg and diastolic pressure exceeds 90 mmHg. Hypertension data in the working area of Nanggalo Padang Health Center in 2018 there are 3224 cases of hypertension. Nonpharmacological management of hypertension, one of which is instrumental music therapy. The purpose of this study was to determine the effect of instrumental music therapy on reducing blood pressure in hypertensive patients in the Working Area of Nanggalo Padang Health Center in 2019. The research method is a quasi-experimental type with one group pretest and posttest design. This research was conducted in the working area of the Nanggalo Padang Public Health Center, Korong Gadang Rw 06 from June to December 2019. The intervention time was 14 days. The population in this study was hypertension sufferers with a total sample of 10 respondents. Data is processed by editing, coding, entry, and cleaning steps. Univariate analysis uses mean, standard deviation and bivariate analysis using paired T-test. The results obtained an average blood pressure before doing instrumental music therapy 157/93 mmHg, while the average blood pressure after doing instrumental music therapy 136/82 mmHg. Paired T-test results obtained a p-value of 0,000 which means, the influence of instrumental music therapy on reducing blood pressure in patients with hypertension. It is hoped that this instrumental music therapy can be included in the puskesmas program as a non-pharmacological treatment that can have a positive effect on lowering blood pressure.